Didactic Intralingual Dubbing of Vertical Videos for EFL Learners: A Didactic Proposal - Elejalde, Aitziber (JET (Journal of English Teaching), 2024)
This paper is focused on the development of a didactic proposal for English students in the Basque Country. Specifically for students in the 1st year of Bachillerato with Spanish and Basque as their L1 and English as their L2 which aims to improve their communication skills, especially oral abilities and pronunciation, through the use of didactic dubbing. This proposal is framed within a project-based learning (PBL), in which the final project is the creation of a vertical video dubbed in English. For this purpose, six sessions have been designed with different group activities that will culminate with the presentation of the video. This didactic unit revolves around social networks and seeks to meet the requirements of current regulations in terms of objectives, contents, competences and evaluation criteria. In addition, transversal elements such as the appropriate use of social networks, fears or interpersonal relationships are worked on. The use of videos in vertical format meets the increasing demand for creating content in this format that adapts to the new mobile devices.